Penanaman Nilai-Nilai Antikorupsi Melalui Pendidikan Islam Di Sekolah Dasar - Sri Isnani Setiyaningsih; Nadia Ayu Salzabilla; Salma Izza Ikfiyana Rahma; Siti Khamidah (CV. SINAR HOWUHOWU, 2026)
This article examines how anti-corruption values can be effectively instilled through Islamic education at the elementary school level using a library research approach. Corruption remains a serious problem in Indonesia, ranking 115 th out of 180 countries in the Corruption Perceptions Index (2023). Islamic education, with its fundamental values such as honesty (shidq), justice ('adl), trustworthiness (amanah), responsibility, patience, and qana'ah, has strong relevance to anticorruption principles. The results show that these values can be implemented through three main models: integration into Islamic Religious Education (PAI) subjects, extracurricular activities, and the cultivation and habituation of values throughout school life. Effective implementation requires curriculum readiness, teacher competence, parental support, and collaboration among all educational stakeholders. This article recommends systematic integration of anti-corruption education into PAI curriculum as a strategic effort to form a generation of integrity and free from corrupt behavior.